2019
DOI: 10.31665/jfb.2019.6191
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound- and hemicellulase-assisted extraction increase β-glucosidase activity, the content of isoflavone aglycones and antioxidant potential of soymilk

Abstract: Soymilk is consumed as such or used in the preparation of tofu, fermented soymilk, and soy yogurt, among others. In this study, hemicellulase-assisted extraction (HAE) and ultrasound-assisted extraction (UAE) were used during soymilk manufacturing. The activity of endogenous β-glicosidases was increased 1.3 and 1.5-fold in soymilk produced upon HAE and UAE, respectively. Likewise, the concentration of isoflavones in the aglycone form increased 1.7 and 2.4 times in samples subjected to HAE and UAE, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Soybean could also be used for making nutritious food products such as cookies, snack foods, bread, soups and pasta due to the rich protein concentration as well as balanced amino acid profile (Edema et al 2005). Silva et al (2019) reported that soybean is also used for producing soymilk, which can be consumed as such or used for preparing fermented soymilk, tofu and soy yogurt.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soybean could also be used for making nutritious food products such as cookies, snack foods, bread, soups and pasta due to the rich protein concentration as well as balanced amino acid profile (Edema et al 2005). Silva et al (2019) reported that soybean is also used for producing soymilk, which can be consumed as such or used for preparing fermented soymilk, tofu and soy yogurt.…”
Section: Introductionmentioning
confidence: 99%
“…Groundnut seeds are good sources of several essential minerals such as calcium, phosphorus, magnesium and zinc as well as vitamin B1 (FAO 2002). Groundnut also contains ample amounts of vitamin E (αtocopherol), which is widely used to prevent oxidative deterioration in lipid-rich foods (de Camargo and Silva et al (2019). Kersting's groundnut (Kerstigiella geocarpa Harms) is considered an underutilized legume; it consists of high amounts of essential minerals, protein and amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Another important strategy for harnessing the potential of the insoluble-bound polyphenols is increasing their bioavailability through auxiliary methods such as enzyme-assisted extraction, fermentation, and germination [23], which increases the ratio of the soluble to insoluble-bound phenolic compounds in a given sample. Other methods to improve the release of IBPP from the cell wall of the plant material include high-pressure-and ultrasound-assisted extraction [24,25]. The use of these methods has a positive impact on their potential health effects and opens new avenues in the development of functional foods and dietary supplements [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrothermal treatment and ultrasound (US) exposure (de Lima, Kurozawa, & Ida, ; Falcão et al, ) can change the isoflavone profile of the feedstock before the production of soybean products. Soaking and US affect the activity of endogenous enzymes involved in the conversion of conjugated isoflavones to their respective aglycones (de Lima et al, ; Falcão et al, ; Silva et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Soaking and US affect the activity of endogenous enzymes involved in the conversion of conjugated isoflavones to their respective aglycones Falcão et al, 2018;Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%